Emotions in medical education: Examining the validity of the Medical Emotion Scale (MES) across authentic medical learning environments. (December 2020) - Duffy, Melissa C.; Lajoie, Susanne P.; Pekrun, Reinhard; Lachapelle, Kevin
Abstract: To advance emotion research in education, there is a need to develop practical and context-relevant measures of emotion and to test the applicability of emotion theories using these measures. In two studies, we examined validity evidence of a self-report scale (the Medical Emotion Scale, MES) designed to measure the unique range of emotions activated within medical education. In Study 1, we administered the MES and conducted interviews with medical trainees ( N  = 15). Content analysis of interviews demonstrated that the MES captured an appropriate range of emotions and that there was alignment between scale responses and interview responses. In Study 2, we measured medical trainees' ( N  = 60) emotions using the MES for three learning environments. Results from principal components analysis revealed a structure of emotions according to valence (negative, positive) and novelty. The findings have implications for the measurement of emotions within technology-rich learning environments and beyond.